Screening for antibacterial activity of Cissampelos pareira L. root extract: an in-vitro study - Girma, Abayeneh (Universa Medicina, 2024)
BackgroundThe recurrence of antibacterial infections after antibiotic treatment necessitates the investigation of alternative therapies against uropathogens. Cissampelos pareira is an Ethiopian medicinal plant that has been used for centuries by traditional healers to treat various diseases. The plant is selected on the basis of its traditional use in treating urinary tract infections by the local community. The objective of this study was to determine traditionally used anti-uropathogenic properties of C. pareira root extracts. Methods C. pareira plant roots collected from Pawe Woreda were shade-dried, powdered, and extracted using chloroform, hexane, acetone, methanol, and ethanol, respectively. The antibacterial activities with different concentrations of the crude extracts were determined using the disc diffusion assay. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of the crude extracts were determined using a two-fold broth dilution method. ResultsThe antibacterial activities of the root extracts against tested organisms as shown by inhibition zone diameters ranged from 7.0±0.1 to 20.8±1.0 mm. The highest inhibition was recorded from the ethanol extract while the lowest was from the chloroform extract.  The MIC and MBC values ranged from 12.5 to 50 µg/mL and 25 to 100 µg/mL, respectively. Ethanolic and methanolic C. pareira root extracts showed the presence of antibacterial compounds (alkaloids, flavonoids, tannins, terpenoids and steroids). ConclusionThis study showed that C. pareira root serves as a potential source for developing new antibacterial drugs against bacteriuria. However, nontoxicity evaluation is recommended for the use of herbals as therapeutic agents in pharmacy.